2018
DOI: 10.3171/2018.3.focus1857
|View full text |Cite
|
Sign up to set email alerts
|

Safety and outcomes of resection of butterfly glioblastoma

Abstract: OBJECTIVEButterfly glioblastoma (bGBM) is a rare type of GBM, characterized by a butterfly pattern on MRI studies because of its bihemispheric involvement and invasion of the corpus callosum (CC). There is a profound gap in the knowledge regarding the optimal treatment approach as well as the safety and survival benefits of resection in treating this aggressive brain tumor. In this retrospective study, authors add to our understanding of these tumors by identifying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
83
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(94 citation statements)
references
References 17 publications
7
83
3
1
Order By: Relevance
“…This observation shows an important limitation of our retrospective study because large tumors were never who was able to show that mass reduction causes favoral neurological outcome and leads to improved functional performance even if the surgical removal comes with higher risk of surgery-associated complications. In line with other authors, we showed a survival benefit for patients who underwent tumor resection [12][13][14]. However, compared to other published works, the extent of survival benefits is distinctly lower in our cohort.…”
Section: Treatment Of Ccgbm-still a Matter Of Debatesupporting
confidence: 90%
See 1 more Smart Citation
“…This observation shows an important limitation of our retrospective study because large tumors were never who was able to show that mass reduction causes favoral neurological outcome and leads to improved functional performance even if the surgical removal comes with higher risk of surgery-associated complications. In line with other authors, we showed a survival benefit for patients who underwent tumor resection [12][13][14]. However, compared to other published works, the extent of survival benefits is distinctly lower in our cohort.…”
Section: Treatment Of Ccgbm-still a Matter Of Debatesupporting
confidence: 90%
“…Therefore, until lately, diagnostic and molecular profiling via tumor biopsy was widely favored over the attempt of gross-total tumor resection. Yet, a growing number of authors have published data highlighting the benefits of resection of glioblastoma of the corpus callosum (ccGBM), specifically regarding improved overall survival without aggravating persistent neurological deficits [12][13][14]. Unfortunately, there is a lack of consistent molecular profiling of the tumors in the previous studies, which leads to a disputable interpretation of the benefits of surgical resection upon survival in this subset of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Percentage of patients impaired per domain, considered as a decrease in a Z-score of more than 1.5 SD, at time points t1 (prior to surgery), t2 (before hospital discharge) and t3 (at long-term follow-up). 10 . Most importantly, patients who underwent biopsy of butterfly glioma experienced significantly shortened OS, ranging from 1.5 to 4.2 months 9,10,12,20 .…”
Section: Discussionmentioning
confidence: 99%
“…However, median survival of patients with butterfly glioblastoma was markedly improved by tumor resection, doubling a patient's remaining life time in comparison to tumor biopsy only; a resection of ≥ 65% of the tumor volume was found to be associated with longer overall survival. Another analysis on the impact of EoR in butterfly glioblastoma was provided by Dayani et al, and they found out that the amount of total tumor reduction, but not EoR within the corpus callosum influenced patients' overall survival (OS) 10 . Chen et al equally observed EoR to be independently associated with longer OS in both, low-and high-grade glioma, whereas no such association was found for corpus callosum involvement which had no significant impact on OS 11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation